Comparative Study on the Effectiveness of Interactive Virtual Reality Simulations Integrating Acehnese Local Wisdom for Mobile-Based Problem-Based Learning - Al-Bahri , Fauzan Putraga; Ismail (Journal Mobile Technologies (JMS), 2023)
Technological advancements have transformed educational practices worldwide. Interactive virtual reality simulations incorporating Acehnese local wisdom represent an emerging educational approach with significant potential. The research examines learning effectiveness enhancement through engaging technology integration, application of Acehnese cultural elements in educational settings, development of interactive problem-based learning environments, and evaluation of effectiveness differences between virtual reality implementations and traditional teaching methods. Virtual reality technology creates immersive environments where users experience simulated settings with realistic interaction capabilities. Acehnese wisdom elements integrated into these environments facilitate deeper cultural understanding among students. The problem-based learning framework encourages collaborative problem-solving through peer engagement and discussion. Research outcomes aim to establish more engaging instructional methodologies while promoting appreciation of Acehnese heritage. The comparative analysis between virtual reality implementations and conventional approaches reveals essential information regarding technological applications in educational contexts. Results demonstrate that virtual reality simulations incorporating Acehnese cultural elements offer innovative solutions for problem-based learning environments, substantially improving student engagement metrics and learning outcome measurements.